PENGARUH MODAL KERJA DAN VOLUME PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Marpaung, Nicholas (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2019)
This research is aimed to determine the level of working capital and the volume of sales to net income, and to determine the effect of working capital on the volume of sales to net income either simultaneously or partially (path analysis) on the Indonesian Stock Exchange in 2010-2014. The research methods used are descriptive and verification methods. Descriptive methods are intended to find out the development of working capital and the volume of sales to net income. While verification methods is intended to find out the influence of working capital, the volume of sales to net income, and to test a theory by testing a hypothesis, wheter it’s accepted or rejected. The coefficient of determination and hypothesis test is calculated by using an application called SPSS 17.0 for windows. These results indicate that partial working capital significantly influences the sales volume. Working capital has a significant effect on net income. Sales volume has a significant effect on net income. Keyword: Working Capital, Volume of Sales, Net Income